Image Restoration Menggunakan Metode Lucy-Richardson Pada Citra Underwater - Sriyanti Boang Manalu (STMIK Budi Darma, 2021)
Image restoration is a step to get a clearer image of a degraded image by only knowing some of the degradation factors of that image. Image restoration is different from improving image quality (image enhancement) even though both of them aim to improve image quality. Image enhancement is more related to the sharpening of certain features in the image, while image restoration utilizes knowledge about the process of degradation to recover the original image. The image restoration aims to eliminate or minimize defects in the image. The goal is almost the same as image repair operations, the difference being the restoration of the image that causes image degradation is known. For the image restoration using the Lucy-Richardson method for image restoration and the method can be the solution to the above problems